KAJIAN PEMASARAN RELASIONAL BAYAM JEPANG (HORENSO) ORGANIK DI INAGREEN FARM, DILEMA ANTARA HARAPAN DAN KENYATAAN - Elly Rasmikayati; Endah Djuwendah; Bobby Rachmat Saefudin; Nur Syamsiyah; Amallia Ridhatillah (Universitas Galuh Ciamis, 2020)
The high demand trend of organic vegetable consumers has triggered an increase in demand from modern retail for organic horenso products at InaGreen Farm, which acts as a supplier of organic horenso for modern retail. However, the high demand was not optimally fulfilled due to various obstacles. The purpose of this paper is: 1) to find out the marketing implementation of InaGreen Farm with modern retail partners and partners, and; 2) know the obstacles faced in order to be able to provide recommendations to InaGreen Farm in the implementation of marketing of organic horenso products with partners and modern retailers. The research design used is qualitative descriptive method. The informants involved in this study were selected using purposive sampling technique. The results showed that: 1) marketing implementation between InaGreen Farm and partners and modern retailers did not run well because there were still things like opportunistic behavior or breach of agreement committed by InaGreen Farm in relational marketing that was intertwined, by not meeting the demand optimally from modern retailers; and 2) the obstacle faced by InaGreen Farm in establishing relational marketing with partners and modern retailers is the low organic horenso production at InaGreen Farm due to the lack of production area owned, there is no written agreement or agreement with partners in running a cooperative relationship.